The Application Of Slow Deep Breating Post Op Herniadectomy Patients With The Application Of Jean Watson's Theory At Muara Beliti Hospital, Musi Rawas Regency In 2022 - Otlina, Otlina; Murwati, Murwati; Sofais, Danur Azissah roeslina (Universitas Dehasen Bengkulu, 2023)
Tuberculosis (TB) is a chronic, recurrent infectious disease that usually affects the lungs, even though the organs are not affected. Caused by Mycobacterium tuberculosis, M. tuberculosis is a small, relatively slow-growing and rapidly acidic rod-shaped organism with a waxy outer capsule, which increases its resistance to destruction. Although the lungs are usually affected, and TB can involve other organs as well. Transmitted by droplet nuclei, airborne droplets are produced when an infected person coughs, sneezes, talks, or sings. Once small droplets can circulate in the air for several hours. Infection can occur when susceptible hosts breathing in air containing droplets, nuclei, and contaminated particles evade the normal defenses of the upper airway to reach the alvroli.Nightingale's concept of placing the environment as the focus of nursing care and the concern where nurses do not need to understand the entire disease process was an early attempt to separate the nursing and medical professions. Nightingale does not look at nurses narrowly who are only busy with the issue of administering medicine and medication, but is more oriented towards the delivery of air, lights, environmental comfort, hygiene, tranquility and nutrition.In this study, the method used is to use a method, namely a nursing process approach based on the chosen nursing theory, the techniques used in data collection, namely by interview, observation, physical examination and conducting nursing care. Data sources obtained or used are primary obtained directly from patients and secondary data obtained from family, health workers and documentation from other examination results to carry out nursing care, while literature study is studying source books related to nursing care given to patients.The purpose of Florance Nightingale's theory in pulmonary TB patients is to improve health services that have a great ability to improve their condition in dealing with disease professionally and aims to bring / deliver individuals to the best condition to be able to carry out activities through basic efforts to influence the environment.